(Dis-)Empowerment in context: a proto-evaluative perspective on welfare reform agendas and their impact, North-West and South. Issue 5 (20th October 2021) - Bode, Ingo; Moro, Giuseppe
ABSTRACT: This article, inspired by the epistemology of critical realism and its approach to assessing social and institutional change, elaborates on the impact of past welfare reform agendas in Europe, taking Italy and Germany as examples. Reading welfare state change through the lens of the concept of empowerment, it argues that such agendas should be studied by considering the nexus of different (coinciding) policies, the transformation of organisational settlements, and the reforms' fit with encultured social expectations. Illustrating how a reform agenda containing a potential to enhance self-determination in the area of work and family life may simultaneously contribute to disempowerment, the article shows how a multidimensional 'proto-evaluative' endeavour may help develop a more holistic understanding of past welfare state change up to the outbreak of the Corona19 pandemic.